1998
DOI: 10.1046/j.1365-2133.1998.02088.x
|View full text |Cite
|
Sign up to set email alerts
|

Early curettage of giant congenital naevi in children

Abstract: Early curettage of giant congenital naevi in new-born infants, if performed during the first few weeks after birth, can have a substantial effect on the pigmentation of the lesions, reducing the number of pigmented cells and leaving only moderate scars. We describe our experience in a series of nine congenital naevi treated by curettage between the first and seventh week after birth. Histological changes that occur in the naevus during the first few days after birth mean that early treatment is needed to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 26 publications
(50 reference statements)
0
24
0
1
Order By: Relevance
“…The former includes laser treatment, curettage, and cryotherapy with dry ice. [11][12][13][14][15] None of these treatments, however, are able to achieve complete excision of nevus. Complete excision is desirable because the possibility of malignant melanoma cannot be excluded.…”
Section: Discussionmentioning
confidence: 95%
“…The former includes laser treatment, curettage, and cryotherapy with dry ice. [11][12][13][14][15] None of these treatments, however, are able to achieve complete excision of nevus. Complete excision is desirable because the possibility of malignant melanoma cannot be excluded.…”
Section: Discussionmentioning
confidence: 95%
“…The best cosmetic results for this technique have been reported when treatment is carried out during the first 2 weeks of life. 16,17 This requires a prompt decision soon after birth, with the resultant pressure on the parents. The cases reported here all showed marked improvement in their appearance after birth, so much so that three of the children had no cosmetic deficit at all in the long term.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medical complication rates were high, with reported scarring in up to 25%, and wound infection in up to 18% . Several small studies have reported dramatic improvements and high levels of patient satisfaction after superficial removal techniques; however, improvements in colour were judged subjectively and immediately postintervention . Furthermore, several reports and studies still advocate early aggressive intervention in CMN with superficial removal techniques with outcomes reported by direct comparison of results to early postnatal pictures .…”
Section: Discussionmentioning
confidence: 99%